2019
DOI: 10.5433/1679-0359.2019v40n5p1937
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oils extracted from clove and lemongrass against pathogenic bacteria isolated from bovine, swine and poultry feces

Abstract: The objective was to verify the antibacterial activity of lemongrass and clove oils against Escherichia coli isolated from poultry feces, Staphylococcus aureus isolated from swine and poultry feces and Salmonella sp. isolated from swine and bovine feces. The antimicrobial activity was evaluated by the disc diffusion test using different concentrations of the oils: 160, 80, 40, 20 and 10 ?l ml -1. The multi-resistance of strains relative to that of conventional antimicrobials was also evaluated by the disk diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…It has been previously reported that clove EO also exhibits significant inhibitory effects against Ps. aeruginosa, S. aureus and E. coli [42].…”
Section: Non-concentrated Hydrolate (H Hd H Sd )mentioning
confidence: 99%
“…It has been previously reported that clove EO also exhibits significant inhibitory effects against Ps. aeruginosa, S. aureus and E. coli [42].…”
Section: Non-concentrated Hydrolate (H Hd H Sd )mentioning
confidence: 99%